On the use of movement-based interaction with smart textiles for emotion regulation - Jiang, Mengqi; Nanjappan, Vijayakumar; ten Bhömer, Martijn; Liang, Hai-Ning (MDPI AG, 2021)
Research from psychology has suggested that body movement may directly activate emotional experiences. Movement-based emotion regulation is the most readily available but often un-derutilized strategy for emotion regulation. This research aims to investigate the emotional ef-fects of movement-based interaction and its sensory feedback mechanisms. To this end, we de-veloped a smart clothing prototype, E-motionWear, which reacts to four movements (elbow flexion/extension, shoulder flexion/extension, open and closed arms, neck flexion/extension), fabric-based detection sensors, and three-movement feedback mechanisms (audio, visual and vibrotactile). An experiment was conducted using a combined qualitative and quantitative ap-proach to collect participants’ objective and subjective emotional feelings. Results indicate that there was no interaction effect between movement and feedback mechanism on the final emo-tional results. Participants preferred vibrotactile and audio feedback rather than visual feedback when performing these four kinds of upper body movements. Shoulder flexion/extension and open-closed arm movements were more effective for improving positive emotion than elbow flexion/extension movements. Participants thought that the E-motionWear prototype were comfortable to wear and brought them new emotional experiences. From these results, a set of guidelines were derived that can help frame the design and use of smart clothing to support us-ers’ emotional regulation.